PEMBINAAN TENAGA KESEHATAN DALAM PENGELOLAAN PERALATAN MEDIS DI RUMAH SAKIT UMUM PAYANGAN, GIANYAR, BALI - Suhartono Suhartono; I Made Agus Mahardiananta; Cokorda Istri Dharmayanti; Kadek Agus Riki Gunawan; I Putu Adi Surya Gunawan (Jurnal Abdi Insani, 2022)
The quality of health services to the community must always be improved as a form of responsibility for health workers. One of the important things in improving the quality is maintaining the quality of medical equipment. Some things that must be considered in medical devices are the measuring value and safety of the device itself. Some of the tools that are often used in hospitals are Oxygen Concentrator, Nebulizer, SPO2, ECG, Defibrillator, Bedside Monitor, Ventilator, Infuse Pump, Syringe Pump, Baby Incubator, Phototherapy, Bubble CPAP, Doppler and Suction Pump. This community service activity is to assist the hospital in taking an inventory of the health equipment they have, making it easier to collect data on which equipment can still be used or must be repaired and conduct training for technicians and medical personnel. The method of activities carried out is observation, lectures, inventory and direct practice of function testing and repair of medical devices. This activity was attended by several technicians and medical personnel from Payangan General Hospital in the hope that all medical personnel will understand the medical equipment that is often used. The results of this activity were several equipment that needed repairs such as tools, ECG, Nebulizer, Baby Incubator, Oxygen Concentrator, Suction Pump, Phototherapy, Bubble CPAP and Doppler. This activity indirectly provides knowledge and experience to medical personnel, with the hope that the service life of all medical equipment will be longer.